GAYA KEPEMIMPINAN TERHADAP PRESTASI KERJA PEGAWAI PADA KOMISI PEMILIHAN UMUM (KPU) KOTA PONTIANAK - Yudistira E.21109087 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
This title is a Leadership Style Influence Job Performance Against Employees In The General Election Commission ( KPU ) Pontianak . The purpose of this study is to investigate and analyze the influence of leadership styles on work performance of employees in the Commission 's Office of Pontianak . Through simple linear regression statistical tests using saturated samples where the number of samples is less than 30 persons , ie 13 people . The results showed that there is a correlation coefficient ( R) of 0664 and the R Square of 0.441 , which means there is very strong and significant effect of variable X to variable Y. For t test obtained tcount 2,994 with a probability value ( sig ) = 0.013 . Sig . smaller than the value of the probability 0:05 or 0.013 > 0.05 , then Ho is rejected and Ha accepted . ttable 2201 with denominator df = 11 and df numerator = 1 , then t count ( 2,994 ) > t table ( 2.201 ) , meaning a significant effect of leadership style on work performance of employees. The conclusion of this study is the leadership style leadership styles assessed by indicators of democracy , authoritarian leadership style , and leadership style affect free employee performance as measured by indicators of quality of work , creativity, work , and timeliness of completing the work . However , not only these factors , but there are many things that can be a factor to measure employee performance . Keywords: leadership style and employee job performance.